2015
DOI: 10.3892/mmr.2015.3269
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products induce glomerular endothelial cell hyperpermeability by upregulating matrix metalloproteinase activity

Abstract: The present study aimed to investigate the effects of advanced glycation end‑products (AGEs) on the permeability of glomerular endothelial cells (GEnCs) and determine whether enhanced permeability was due to degradation of tight junction (TJ) complexes by matrix metalloproteinases (MMPs). Cultured monolayers of GEnCs were exposed to AGEs at different doses and treatment durations in the presence or absence of the organic MMP‑2/9 inhibitor (2R)‑2‑((4‑biphenyl sulfony‑l)amino)‑3‑phenylproprionic acid) (BiPs). Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Hyperglycemia (HG) can rapidly increase systemic endothelial and glomerular barrier permeabilities in vivo. Such changes have also been amply demonstrated in the absence of insulin in endothelial monolayers in vitro [3][4][5]. Therefore, the endothelium plays an important role in the glomerular barrier upon HG [1,6].…”
mentioning
confidence: 99%
“…Hyperglycemia (HG) can rapidly increase systemic endothelial and glomerular barrier permeabilities in vivo. Such changes have also been amply demonstrated in the absence of insulin in endothelial monolayers in vitro [3][4][5]. Therefore, the endothelium plays an important role in the glomerular barrier upon HG [1,6].…”
mentioning
confidence: 99%
“…Microvascular barrier dysfunction and endothelial hyperpermeability leading to tissue edema and organ dysfunction are critical in the pathogenesis of these diseases. Although several studies have reported that AGEs contribute to elevated vascular endothelial monolayer permeability and microvascular permeability [2, 21, 25, 26], the mechanisms involved in these processes are complex and remain to be determined. Our study first confirmed the participation of mDia1 in endothelial hyperpermeability in response to AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MMPs have their own inhibitors, TIMPs. 56,57 An overview of TIMPs and their specific MMP substrates is shown in Table 1.2. TIMPs regulate cell functions through MMP-dependent as well as MMP-independent mechanisms, including cell proliferation, apoptosis and differentiation.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…52 Literature provides lots of evidence that AGEs are able to induce MMP production. 29,[53][54][55][56][57][58][59][60][61][62][63][64][65][66] In vitro studies have shown AGEinduced MMP expression in various cells that are associated with vascular complications 29,57,62,65 We studied associations between circulating levels of proteinbound N ε -(carboxymethyl)lysine (CML), N ε -(carboxyethyl)lysine (CEL), 5-hydro-5methylimidazolone (MG-H1), pentosidine and MMP-1, -2, -3, -9, and -10, and TIMP-1. We showed that CML, an extracellular AGE and a major ligand of the receptor of AGE (RAGE), was positively associated with circulating MMP-2 and inversely with MMP-9 after adjustment for potential confounders.…”
Section: Advanced Glycation Endproducts and The Mmp-timp Systemmentioning
confidence: 99%
See 1 more Smart Citation